Synthesis of Ruthenium Catalysts with a Chiral Arene Ligand Derived from Natural Camphor - Pototskiy, Roman A.; Boym, Mikhail A.; Nelyubina, Yulia V.; Perekalin, Dmitry S. (Synthesis, 2021)
A ruthenium complex with a chiral arene ligand [(camphor–arene)RuCl2]2 was synthesized by the reaction of RuCl3·nH2O with a chiral diene which was obtained from natural camphor in three steps. This complex catalyzed the asymmetric hydrogenation of acetophenone (64–85% ee), but decomposed in catalytic reactions involving C–H activation of 2-phenylpyridine or benzoic acid derivatives.
Keywords: ruthenium; arene complexes; asymmetric catalysis; camphor; C–H activation